The Role of Remittance in the Development of Migrant Origin Areas in Parigi Moutong Regency, Central Sulawesi Province - Syamsuddin HM; KHaeruddin Thaha; Rahmawati Atjo; Laendatu Paembonan (Institute of Computer Science (IOCS), 2021)
This study aims to analyze the effect of remittances on development in the area of ​​origin of migrants, the impact of remittances on the welfare of households of origin, the use of remittances by households of migrant origin and to analyze the difference in remittance values between international migrants and regional migrants. The method of determining the sample using snowball sampling. The analytical method used is cross tabulation and Chi-Square analysis. The results show that remittances of migrant workers contribute to development in the migrant workers' origin areas. Most (57.3%) the proportion of remittances of migrant workers is used to meet daily consumption needs. While the other 47.2 percent is used for investment in education, health, gardens, vehicles and building houses. There is a positive relationship between the amount of remittances sent by migrant workers and the allocation of remittances for productive business activities. There is a very significant difference between the remittances of international migrant workers and the remittances of internal migrant workers.